Question Solved1 Answer 3 f(x) Na 2 -3 -3 g(x) -2 Consider the two graphs above. What are the following limits? (If a limit does not exist, write DNE.) lim f (x) 21 lim g(x) -1 Note that the two functions f (x) and g(x) are identical except for at x = 1 Is the following statement TRUE or FALSE? For any function h (2), the limit lim h (x) does not depend on the value of h(x) at x = a , or even whether h (a) is defined or not. (Write "TRUE" or "FALSE".).

82NSHT The Asker · Calculus

Transcribed Image Text: 3 f(x) Na 2 -3 -3 g(x) -2 Consider the two graphs above. What are the following limits? (If a limit does not exist, write DNE.) lim f (x) 21 lim g(x) -1 Note that the two functions f (x) and g(x) are identical except for at x = 1 Is the following statement TRUE or FALSE? For any function h (2), the limit lim h (x) does not depend on the value of h(x) at x = a , or even whether h (a) is defined or not. (Write "TRUE" or "FALSE".).
More
Transcribed Image Text: 3 f(x) Na 2 -3 -3 g(x) -2 Consider the two graphs above. What are the following limits? (If a limit does not exist, write DNE.) lim f (x) 21 lim g(x) -1 Note that the two functions f (x) and g(x) are identical except for at x = 1 Is the following statement TRUE or FALSE? For any function h (2), the limit lim h (x) does not depend on the value of h(x) at x = a , or even whether h (a) is defined or not. (Write "TRUE" or "FALSE".).
See Answer
Add Answer +20 Points
Community Answer
ODVXEQ The First Answerer
See all the answers with 1 Unlock
Get 4 Free Unlocks by registration

Soln: Basic concepts(i) lim_(x rarr c)f(x) exist and equal to l if and only if lim_(x rarrC^(-))f(x)=lim_(x rarrC^(+))f(x)=l in this case we writelim_(x rarrC^(-))f(x)=lim_(x rarrc^(+))f(x)=lim_(x rarr c)f(x)=l.Given the graph isNo Klim_(x rarr1^(-))f(x)=2, since in the graph of f(x) if we approach the point x=1 from left side the graph of f(x) tends to 2 .and lim f(x)=2, since in the graph of f(x) x rarr1^(+)if we approach the point x=1 from rigth side the graph of f(x) tends to 2 .since lim_(x rarr1^(-))f(x)=lim_(x rarr1^(+))f(x)=2; then lim_(x rarr1^(-))f(x) existand lim_(x)f(x)=2Thus lim_(x rarr1)f(x)=2 x rarr1Againlim_(x rarr1^(-))g(x)=2; since in the graph of g(x) ... See the full answer